A Better Engineering Design for Safety Environment - Yap, Chew Shan; Tung, Kean Wei; Ramalingam, Mritha; Puviarasi, R.; Ernawan, Ferda; Chinnavan, Elanchezhian (Academic Publications, 2017)
Security is an important concern in day to day life, far augmented when related to sensitive data, such as private information. In a smart home scenario, to ensure high confidentiality,this paper focuses on thedesign of a better engineering application using solar energy for the home security system. This design involvesbiometric systems such as voice and speech recognition. Additionally, the Graphical User Interface is designed for the user to monitorthe security status.This paper surveys the security threats existent in society environments with possible solutions to mitigate the threats. Lastly, this work attempts to integrate the solutions in a cohesive form to be applied to any society environment that wishes to keep better security of home environment. The solar energy is utilized as the power supply. The performance of this microcontroller based voice integrated design is evaluated in terms of accuracy and velocity in various environments.